New and little-used morphological characters in Polydesmida (Diplopoda) - Robert Mesibov (Soil Organisms, 2009)
Polydesmida (Dalodesmidae and Paradoxosomatidae) vary in the structure of spiracles, spinnerets, male leg setae and integument fine sculpture. Although this variation is only clearly seen with scanning electron microscopy, some variations are apparent at low magnification. Spiracle, spinneret and fine sculpture variations are found in both sexes and are thus useful in identifying females. The variations described here are taxonomically useful at the species- and genus-group levels. Their functional significance is unknown.